VEHICLE REPAIR MONITORING INFORMATION SYSTEM FOR OPERATIONAL VEHICLES AT PT SU - Sultan Imam Fajri; Darius Antoni; Evi Yulianti (Ninety Media Publisher, 2026)
Rapid developments in information technology have encouraged companies to improve operational efficiency through the implementation of integrated information systems. In transportation and logistics companies, vehicle maintenance management plays an important role in supporting operational continuity. PT SU currently still uses Microsoft Excel to record and monitor vehicle repairs, resulting in several problems such as data duplication, delays in reporting, difficulties in monitoring repair progress, and the risk of data loss. Therefore, this study aims to design and develop a web-based operational vehicle repair monitoring information system using the Web Engineering method. The development process consists of communication, planning, modeling, construction, and deployment stages. Unified Modeling Language (UML) was used to model system requirements, including use case diagrams and Entity Relationship Diagrams (ERD). The system was developed using PHP, MySQL, and Apache server through XAMPP. The developed system provides several features, including vehicle data management, repair requests, repair status monitoring, repair reports, and repair history management. System testing was conducted using black-box testing, performance testing, usability testing, and User Acceptance Testing (UAT). The testing results showed that all system functions operated properly according to user requirements. Performance testing indicated that the average response time was below 3 seconds, while usability testing showed positive results with ease of use reaching 90% and monitoring effectiveness reaching 92%. The developed system successfully improved repair data management, reporting efficiency, monitoring transparency, and coordination between departments at PT SU.